Social inclusion of persons with disability in employment: what would it take to socially support employed persons with disability in the labor market? - Chumo, Ivy; Kabaria, Caroline; Mberu, Blessing (Frontiers in Rehabilitation Sciences, 2023)
Abstract Introduction Unemployment is one of the major challenges facing persons with disabilities (PWD) worldwide. The challenge does not lie with a PWD, but with systems that are not built with inclusivity in mind by employers. As such the work of inclusion is not inviting PWD to do more but to make a difference through social support. Most research on inclusion in the employment of PWD has been focused upon the labour ‘supply’ side of the employment spectrum and to the best of our knowledge and in informal settlements, no specific studies approached these employment and inclusion issues from the perspective of employers’ mindset. As such our question in this study, simply put, is; ‘‘what would it take’ to socially support employed PWD in informal settlements building from the perspectives of employers? Methods This paper used data from in-depth interviews with 38 service providers in the education, health, water, sanitation, and solid waste management sectors and 2 sub-County officials in two informal settlements in Nairobi, Kenya. Data from transcripts were analyzed by the research team using content analysis. Results The social support offered to employed PWD included listening to them with concern; identifying their strengths and obstacles; planning for them based on their qualities, knowledge and experience and linking them with existing opportunities; creating specific opportunities and facilitating their access to opportunities; gradual withdrawal of support by support group and lastly, compromise by employers with PWD inclusion strategies. Study participants described how misdirected and inadequate resources; dissatisfaction and unhappiness and conflicts at the work place associated with non-inclusion were constraints to social support. Essential to the functioning of an inclusive workplace for PWD were communication, coordination, sharing of the workload and supporting individual persons. Conclusion We conclude that no one wants to be tolerated or pitied at work. PWD, just like those without disabilities, want to be recognized for their talents and accomplishments, as such employers and other actors in the labour market should consider social support of employed PWD.